A New Case of Scientific Dishonesty in the Field of Parapsychology - Nahm, Michael (Journal of Scientific Exploration, 2021)
The present article informs about a case of prolonged scientific dishonesty in the field of parapsychology. It emerged that Alejandro Parra, an active member of the parapsychological community since about three decades, has published substantially plagiarized books and articles since at least 2007. Currently, I am aware of 20 publications that contain plagiarized sections or consist almost entirely of plagiarism. In the following, I present striking examples of such plagiarized texts and provide background information about the development of this case. Parra even presented research results obtained by others as his own research results, which amounts to data fabrication. Therefore, I conclude one cannot trust any of his books and articles. Even Parra’s publications that contain data obtained in surveys or experimental studies must be disregarded by the scientific community unless the validity of their raw data has been very carefully established by examinations performed by others.